Răspuns :
Răspuns:
Explicație pas cu pas:
a)
[tex]3^{17} + 3^{9}:3^{6} - 3^{16}*3^{5}:3^{4} = 3^{17} + 3^{9-6} - 3^{16+5-4} = 3^{17} + 3^{3} - 3^{17} = 3^{3} = 27[/tex]
b)
[tex](5^{14}*3^{17}):25^{7} + 3^{9}:3^{6} - (3^{2})^{8}*3^{5}:3^{4} = (5^{14}*3^{17}):(5^{2})^{7} + 3^{9-6} - 3^{2*8+5-4} = (5^{14}*3^{17}):5^{14} + 3^{3} - 3^{17} = 3^{17} + 3^{3} - 3^{17} = 3^{3} = 27[/tex]
c)
[tex](2^{2}*3)^{17}:2^{34} + 3^{9}:27^{3} - 9^{8}*3^{5}:3^{4} = 2^{34}*3^{17}:2^{34} + 3^{9}:(3^{3})^{3} - (3^{2})^{8}*3^{5}:3^{4} = 3^{17} + 3^{9}:3^{9} - 3^{2*8+5-4} = 3^{17} + 1 - 3^{17} = 1[/tex]
d)
[tex]3^{5} + 3^{5} - (3^{2})^{3} + 3^{5} = 3*3^{5} - 3^{2*3} = 3^{6} - 3^{6} = 0[/tex]